134k views
2 votes
2t+6=3t-6 find the value of t

User Charo
by
5.8k points

2 Answers

2 votes

Answer:

t = 12

Explanation:

Goal : move all the "t" terms to one side and all the constants to the other side.

2t+6=3t-6 (subtract 6 from both sides)

2t = 3t - 6 - 6

2t = 3t -12 (subtract 3t from both sides)

2t - 3t = -12

-t = -12 (multiply both sides by -1)

t = 12

User Strada
by
6.4k points
4 votes

Answer:

t = 12

Explanation:

2t+6=3t-6

Subtract 2t from each side

2t-2t+6=3t-2t-6

6 =t -6

Add 6 to each side

6+6 = t-6+6

12 = t

User Ldrut
by
6.4k points